Pulmonary lymphangioleiomyomatosis associated with aggressive renal angiomyolipoma. Issue 1 (2nd January 2018) - Cooper, Allison; Baugh, Laura; Kelley, Shannon; Huang, Howard; Guileyardo, Joseph
ABSTRACT: Lymphangioleiomyomatosis (LAM) is a rare cystic pulmonary disease that may occur in association with mutations in the tuberous sclerosis genes or arise sporadically. The histologic hallmark of the disease is the "LAM" cell, a spindled to epithelioid smooth muscle-like cell that bears morphologic and immunohistochemical resemblance to the perivascular epithelioid cell tumors (PEComas). The origin of the "LAM" cell is unknown; emerging theories suggest that a member of the PEComa family, the renal angiomyolipoma, may be the primary source and that both LAM and angiomyolipomas are associated with the genetic syndrome tuberous sclerosis. We present a young woman with LAM with an aggressive renal angiomyolipoma confirmed at autopsy.